Improving the administrative mechanism for attracting and utilizing talents in the public sector: From the case of Ho Chi Minh City - Nguyen, Vo Anh (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
This research article focuses on the administrative mechanism for attracting and utilizing talent in the public sector in Vietnam in general and Ho Chi Minh City in particular. Based on the current practical mechanism, the article proposes suggestions to improve the administrative mechanism for attracting and utilizing talent in the public sector so that talent attraction activities in the public sector can be more effective.